Pulmonary Function Test of Compressor Divers in Sekotong Subdistrict, West Lombok, West Nusa Tenggara - Widiastuti, Ida Ayu Eka; Yoga Pamungkas Susani; Putu Suwita Sari; Basuki Rahmat (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Diving activities using tire compressors, as practiced by some traditional fisherman-divers along the coast of Lombok Island when hunting fish and other marine products can cause lung dysfunction. The purpose of this study was to evaluate lung function in traditional divers who use tire compressors in Sekotong District, West Lombok, and to identify possible respiratory disorders arising from such diving activities. This research was an observational analytic study with a cross-sectional design. The data collected consisted of pulmonary function test results obtained through spirometry examination, including Forced Vital Capacity (FVC), Forced Expiratory Volume in 1 second (FEV₁), and the FEV₁/FVC ratio. Descriptive analysis consists of FVC, FEV₁, and FEV₁/FVC ratio values and their interpretations. The results showed that the FVC value was 25.6% lower than the predicted value, while the FEV₁ value was 21.2% lower than the expected value. Most of the subjects (18 people) experienced restrictive-type pulmonary disorders (60%), which was higher than the proportion of subjects with normal pulmonary function (36.7%), while 3.3% experienced obstructive-type pulmonary disorders. Traditional divers who use tire compressors are at risk of reduced vital capacity and forced expiratory volume in one second.